Regulation of gene expression and RNA editing in Drosophila adapting to divergent microclimates. Issue 1 (December 2017) - Yablonovitch, Arielle; Fu, Jeremy; Li, Kexin; Mahato, Simpla; Kang, Lin; Rashkovetsky, Eugenia; Korol, Abraham; Tang, Hua; Michalak, Pawel; Zelhof, Andrew; Nevo, Eviatar; Li, Jin
Abstract Determining the mechanisms by which a species adapts to its environment is a key endeavor in the study of evolution. In particular, relatively little is known about how transcriptional processes are fine-tuned to adjust to different environmental conditions. Here we studyDrosophila melanogaster from 'Evolution Canyon' in Israel, which consists of two opposing slopes with divergent microclimates. We identify several hundred differentially expressed genes and dozens of differentially edited sites between flies from each slope, correlate these changes with genetic differences, and use CRISPR mutagenesis to validate that an intronic SNP inprominin regulates its editing levels. We also demonstrate that while temperature affects editing levels at more sites than genetic differences, genetically regulated sites tend to be less affected by temperature. This work shows the extent to which gene expression and RNA editing differ between flies from different microclimates, and provides insights into the regulation responsible for these differences. Environmental adaptation is generally studied at the genomic level, but it may also be driven by transcriptional processes. Here, the authors investigate variation in gene expression and RNA editing across diverging populations ofDrosophila melanogaster from two microclimates.